Bacteriophage conversion of spore-negative mutants to spore-positive in Bacillus pumilus. - Bramucci, M G (1977)
A pseudolysogenic phage, PMB1, was isolated from soil on the basis of its ability to increase the sporulation frequency of the oligosporogenic Bacillus pumilus strain NRS 576 (sporulation frequency, less than 1%). Several spore-negative mutants (sporulation frequency, less than 10-8) derived from strain NRS 576, which were converted to spore positive by infection with PMB1, were subsequently identified. PMB1 repeatedly grown on a given spore-negative mutant (e.g., GW2) converted GW2 cells to spore positive. Each plaque-forming unit initiated the conversion of a spore-positive clone in semisolid agar overlays. GW2 cells remained spore positive as long as they maintained PMB1. Return of PMB1-converted cells to the orginal spore-negative phenotype correlated with loss of PMB1. In liquid media, PMB1 infection increased the sporulation frequency of mutant GW2 over 106-fold. More than half of the spore-negative mutants we isolated from strain NRS 576 were converted to spore positive by PMB1 infection. PMB1-induced spores of the spore-negative mutant GW2 were somewhat more heat sensitive than uninfected or PMB1-infected spores of the spore positive parent of GW2. PMB1-induced spores of GW2 do not differ from wild-type spores in morphology by phase-contrast microscopy, dipicolinic acid content, or rate of sedimentation through Renografin gradients.